Ancient civilizations - Fullman, Joe. (New York, New York : DK Publishing, 2013)
Introduces young readers to some of the most fascinating ancient civilizations in the world's history and the legacies they left behind, from the intriguing world of pharaohs in Ancient Egypt, to the arts of Greece and Rome, to the amazing culture of the Mayans.
First steps to civilization -- Digging up the past -- Mesopotamia -- Kingdoms of ancient Egypt -- Life in ancient Egypt -- Afterlife in ancient Egypt -- Indus Valley civilization -- Bronze Age and Iron Age Europe -- Minoans and Mycenaeans -- Nubia -- America's first civilizations -- Ancient China -- Writing -- The Phoenicians -- The Maya -- Assyria and Babylon -- The Persian Empire -- The Silk Road -- Ancient Greece -- Ancient Greek society -- Alexander and the Hellenistic age -- Money -- Ancient Rome -- Life in ancient Rome -- The Roman army -- Entertainment -- Mauryan and Gupta India -- Moche and Nazca -- Greatest cities -- Timeline -- Ancient innovations -- Greatest rulers.
At head of title: Eyewitness.
Includes index.
Hardcover edition contains fold-out wall chart and clip-art CD.
Keywords: Civilization, Ancient -- Juvenile literature; History, Ancient -- Juvenile literature